O jornalismo colaborativo no telejornal com as novas mídias digitais - Cajazeira, Paulo Eduardo Silva Lins (2011)
Whereas the advent of new digital technologies, this research studies the viewer's participation / collaboration through collaborative content images recorded on digital media: cell phones or cameras and inserted into the structure of the text in TV journalism.The relevance of this research is to examine changes in the production of news programs with participation of the public considering the following assumptions: 1) the exchange of communicative roles assumed by intended recipients and its evidece in the construction of the sentence and determine a change in production routines the television news with the creation of new media enviroments techno-digitals, 2) public participation is responsible for simulating a profile represented by the display of images recorded by audiovisual own viewers/collaborative and manipulated by television news. The aim is thus to verify the selection criteria for the statements made by (journalists) and recipients (public) through the support of social spaces created by the companies announced on the evening news on TV and the internet